2021
DOI: 10.1093/ajcn/nqaa372
|View full text |Cite
|
Sign up to set email alerts
|

The effect of daily protein supplementation, with or without resistance training for 1 year, on muscle size, strength, and function in healthy older adults: A randomized controlled trial

Abstract: Background Protein supplementation alone or combined with resistance training has been proposed to be effective in counteracting age-related losses of muscle mass and strength. Objectives To investigate the effect of protein supplementation alone or combined with light-intensity or heavy-load resistance exercise on muscle size, strength, and function in older adults. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 68 publications
5
50
2
5
Order By: Relevance
“…The results of the present study support previous findings that resistance training should be recommended as a strategy to counteract the age‐related losses of muscle mass and strength 8‐13 as well as for reducing body fat in both elderly men and women with a minor advantage for men with respect to muscle strength and body fat improvements. It would be interesting in future studies to investigate whether these sex differences are caused by biological or psychosocial differences in order to design the most effective intervention for men and women.…”
Section: Perspectivessupporting
confidence: 90%
See 1 more Smart Citation
“…The results of the present study support previous findings that resistance training should be recommended as a strategy to counteract the age‐related losses of muscle mass and strength 8‐13 as well as for reducing body fat in both elderly men and women with a minor advantage for men with respect to muscle strength and body fat improvements. It would be interesting in future studies to investigate whether these sex differences are caused by biological or psychosocial differences in order to design the most effective intervention for men and women.…”
Section: Perspectivessupporting
confidence: 90%
“…Further, it is well documented that the relative age‐related reduction in these parameters is similar in men and women 1,6,7 . Resistance training has been established as an effective strategy to counteract the age‐related loss of muscle mass and strength in both moderately old and very old individuals, 8‐13 but there are still some discrepancies on whether the benefits of resistance training differ between men and women. Previous literature has shown either similar effects of resistance training, 11,14‐18 lower effects, 19‐21 or even greater effects in women compared with men 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…The study showed weak but significant systematic variations in the human fecal metabolome related to BMI, physical fitness, and blood plasma LP levels. The subjects of this study are healthy older adults, include 83 males (70+/−5 age) and 80 females (70+/−5 age), recruited in the Counteracting Age-related Loss of Skeletal Muscle Mass (CALM) study [20]. The CALM study was designed to investigate the effect of increased protein supplementation and physical exercise on the general health and well-being of community-dwelling relatively healthy older Danes.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have the strength that adaptation to a given protein intake level would be inherent, yet they often suffer from several confounding factors, limiting the translation into other settings and making it impossible to use the results for assessing protein requirements. Longitudinal intervention studies can be applied to examine the cause-effect relationship and/or dose-response relationship between protein intake and most often physiological and functional outcomes, such as muscle mass, muscle strength and physical function, which is particularly relevant to older adults (43)(44)(45)(46)(47)(48) .…”
Section: Epidemiological Studies Of Protein Intakementioning
confidence: 99%
“…Intervention studies. Several randomised controlled intervention studies have investigated whether higher protein intake increases muscle mass in older adults (43)(44)(45)(46)(47)(48) (Table 5). Some studies were unable to show a beneficial effect of increasing dietary protein intake above their average intake of ∼1•2 g/kg/d on muscle accretion or maintenance in older adults (43,44,48) .…”
Section: Higher Protein Intake Was Associated With Alm At Baseline and Follow-upmentioning
confidence: 99%